2021
DOI: 10.1155/2021/3726058
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Ten-Gene Signature of DNA Damage Response Pathways with Prognostic Value in Esophageal Squamous Cell Carcinoma

Abstract: Molecular prognostic signatures are critical for treatment decision-making in esophageal squamous cell cancer (ESCC), but the robustness of these signatures is limited. The aberrant DNA damage response (DDR) pathway may lead to the accumulation of mutations and thus accelerate tumor progression in ESCC. Given this, we applied the LASSO Cox regression to the transcriptomic data of DDR genes, and a prognostic DDR-related gene expression signature (DRGS) consisting of ten genes was constructed, including PARP3, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…GTF2H3 has been demonstrated to serve as a marker gene for esophageal squamous carcinoma [30,31], but there is uncertainty regarding its role in GC. In a study by Zhuang et al in 2021, it was suggested that ERCC8 may in uence GC development by regulating the progression of the PI3K / AKT / mTOR pathway [31]. Also in this study, CUL5 was found to possibly play an important role in DDR mediated by miRNAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GTF2H3 has been demonstrated to serve as a marker gene for esophageal squamous carcinoma [30,31], but there is uncertainty regarding its role in GC. In a study by Zhuang et al in 2021, it was suggested that ERCC8 may in uence GC development by regulating the progression of the PI3K / AKT / mTOR pathway [31]. Also in this study, CUL5 was found to possibly play an important role in DDR mediated by miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Xuan et al 2021 suggested that defects in DDR and DNA repair pathways can induce rRNA instability that may ultimately lead to cancer development [29], which is consistent with our ndings that rRNA-related functions and DDR are closely linked in GC. GTF2H3 has been demonstrated to serve as a marker gene for esophageal squamous carcinoma [30,31], but there is uncertainty regarding its role in GC. In a study by Zhuang et al in 2021, it was suggested that ERCC8 may in uence GC development by regulating the progression of the PI3K / AKT / mTOR pathway [31].…”
Section: Discussionmentioning
confidence: 99%